(3QSGdI aj JLhjO GdbQBfs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hHYO agPg QSGdI JJYdb HJLhjO GdbQBf efJNHI ef cJH eHShWI aj gPG Gdaf GdHGH GdChd aj GdGSJYGPIs
(3BNQgG (B:s
(3ajLH CNPg ef TjN cGed eGgQ aj gPG Gdaf dFdG jchf ef GdBNSQjf CYeGdG GdPjf Vd SYjge aj GdMjhI GdOfjG hge jMSHhf Cfge jMSfhf UfYGs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
(3JYdjbGJs
Keywords: (3GdbQGAGJ hGdJLhjOs